P211 Exacerbation frequency and maintenance treatment of COPD in UK clinical practice. (2nd December 2011) - Thomas, M; Radwan, A; Stonham, C; Marshall, S
Abstract : Introduction and Objectives: COPD exacerbations are associated with high morbidity, mortality and costs. Prevention of exacerbations is recommended as a key goal of COPD management. Pharmacotherapy shown to reduce exacerbation frequency includes long acting beta agonists (LABA), long acting antimuscarinics (LAMA) and inhaled corticosteroids (ICS). There have been suggestions of a "frequent exacerbator" phenotype across severity. Methods: Retrospective observational study of 511 patients with COPD diagnosed during or before 2007. Three years' data per patient on exacerbation frequency, therapies and resource use were collected by trained researchers from routine medical records in 10 general practices in England. COPD severity was defined as: very severe (FEV1 <30% predicted, n=52), severe (30–49%, n=145) and moderate (50–79%, n=314). Exacerbation frequency was annualised and stratified by: 0/year ("non-exacerbators"), >0<3/year and =3/year ("frequent exacerbators"). Results: Mean (SD) annual exacerbation frequency: 1.1 (1.1) in moderate, 1.7 (1.6) in severe and 2.2 (2.0) in very severe COPD. 69 (14%) were frequent exacerbators and 97 (19%) were non-exacerbators. The proportion of frequent exacerbators increased with severity (9% moderate, 19% severe, 29% very severe). 14% did not receive any LABA, 25% any LAMA and 12% any ICS medication during the 3-year study period. "Triple therapy" with all three classes was received by only 67% of the frequent exacerbators. The percentage of patients with zero exacerbations/year fell as severity increased (25% moderate, 11% severe, 8% very severe). 61% received a LABA and/or LAMA with ICS (56% moderate, 75% severe and 100% very severe). 32% did not receive ICS during the study period (35% moderate, 25% severe and 0% very severe). The median number of primary care visits was 1.33 for patients with 0, 2.67 for >0<3 and 6.67 for =3 exacerbations/year. Conclusions: The "frequent exacerbator" phenotype occurs in patients of all levels of severity in community practice in the UK. Health resource use is high in frequent exacerbators. These patients frequently do not receive optimum therapy. The exacerbation history can potentially guide maintenance treatment of patients at all levels of COPD severity.